2002
DOI: 10.1016/s1534-5807(02)00142-9
|View full text |Cite
|
Sign up to set email alerts
|

DWnt4 Regulates Cell Movement and Focal Adhesion Kinase during Drosophila Ovarian Morphogenesis

Abstract: Cell motility is regulated by extracellular cues and by intracellular factors that accumulate at sites of contact between cells and the extracellular matrix. One of these factors, focal adhesion kinase (FAK), regulates the cycle of focal adhesion formation and disassembly that is required for cell movement to occur. Recently, Wnt signaling has also been implicated in the control of cell movement in vertebrates, but the mechanism through which Wnt proteins influence motility is unclear. We demonstrate that Dros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 56 publications
11
132
0
1
Order By: Relevance
“…With respect to DWnt4, we find that it binds to Fz, Dfz2, and Dfz4. This agrees with the phenotypes of DWnt4 and Dfz2 in the ovary: a cell migration defect seen for both the ligand and the receptor (55).…”
Section: Implications Of the Interactions Between Different Wnts Andsupporting
confidence: 88%
“…With respect to DWnt4, we find that it binds to Fz, Dfz2, and Dfz4. This agrees with the phenotypes of DWnt4 and Dfz2 in the ovary: a cell migration defect seen for both the ligand and the receptor (55).…”
Section: Implications Of the Interactions Between Different Wnts Andsupporting
confidence: 88%
“…PKC activation is another recently described mechanism of Wnt-dependent cell motility, associated with the activity of Wnt-5a on melanoma cells (26), DWnt-4 on Drosophila ovarian epithelial cells (25) and convergent extension movements in Xenopus (27). These processes are thought to involve Dvl (25,27). Thus far, we have not obtained evidence of Wnt-dependent PKC activation in our CHO cell model system.…”
Section: Dvl-2 Regulates Wnt3a-dependent Motilitymentioning
confidence: 68%
“…2 We presume that extraneous factors are present in the L and perhaps also Wnt-3a CM that account for this activity and likely contribute to the motility elicited by the CM in the transwell assay. PKC activation is another recently described mechanism of Wnt-dependent cell motility, associated with the activity of Wnt-5a on melanoma cells (26), DWnt-4 on Drosophila ovarian epithelial cells (25) and convergent extension movements in Xenopus (27). These processes are thought to involve Dvl (25,27).…”
Section: Dvl-2 Regulates Wnt3a-dependent Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for this may have to do with the multifunctional nature of Frizzled receptors. Genetic studies in Drosophila have shown that DFz1 and DFz2, which are developmentally redundant for canonical signaling, distinctly function in planar cell polarity (43,44) and cell motility, respectively (43,45). Because of this multifunctionality, the same Frizzled receptor may bind more than just one class of Wnt ligands.…”
Section: Discussionmentioning
confidence: 99%